2018
DOI: 10.1155/2018/7463796
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salivary Adipokines Resistin, Visfatin, and Ghrelin as Type 2 Diabetes Mellitus Biomarkers

Abstract: Type 2 diabetes mellitus (T2DM) is emerging as a metabolic epidemic worldwide. Pathologically, dysregulation of many biological pathways precedes hyperglycemia and the clinical diagnosis of T2DM. Changing trajectories along the process of T2DM development necessitates frequent measurement of biomarkers for early identification of at-risk individuals and successful prevention. Increase in circulating inflammatory adipokines has been suggested as predictive of T2DM. Human saliva is an easily accessible biospecim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Oral administration of quercetin and metformin caused significant reduction (p < .05) of the blood glucose level within the range of 27.8% and 46.3%. Our results corroborate with the findings ofSrinivasan, Meadows, and Maxwell (2018), who reported a similar antidiabetic activity of quercetin in STZ-induced diabetic rats through enhanced insulin secretion from pancreatic β-cells Eid and Haddad (2017). also attributed the antidiabetic effect of quercetin to the inhibition of intestinal glucose absorption and improved glucose utilization in peripheral tissues.…”
supporting
confidence: 92%
“…Oral administration of quercetin and metformin caused significant reduction (p < .05) of the blood glucose level within the range of 27.8% and 46.3%. Our results corroborate with the findings ofSrinivasan, Meadows, and Maxwell (2018), who reported a similar antidiabetic activity of quercetin in STZ-induced diabetic rats through enhanced insulin secretion from pancreatic β-cells Eid and Haddad (2017). also attributed the antidiabetic effect of quercetin to the inhibition of intestinal glucose absorption and improved glucose utilization in peripheral tissues.…”
supporting
confidence: 92%
“…Numerous studies have reported a close correlation between adipocytokines (such as leptin, adiponectin, visfatin, and apelin) and the incidence of T2DM and IR [17][18][19]. Chemerin is a newly identified adipocytokine, and recent cell, animal, and clinical studies have shown that serum chemerin levels are correlated with obesity, diabetes, IR, and metabolic syndrome [8,11,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…96 Minimal differences in TNF-α concentration (50 pg/mL increase in diabetic participants) were observed between the diabetic participants and healthy controls. The difference in outcomes from both studies could be possibly attributed to the fact that participants in the Srinivasan et al 96 were self-reported type 2 diabetics whereas participants in the Tvarijonaviciute et al 29 were diagnosed type 2 diabetics based off the American Diabetes Association criteria. Given these inconsistencies, more research needs to be conducted on TNF-α as a salivary biomarker of type 2 diabetes in order to determine its clinical utility.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 91%
“…88,89,91 Despite the established method of collecting TNF-α through serum samples, recent interest in measuring salivary samples has emerged. 29,47,86,91,96 Mentioned prior, Tvarijonaviciute et al 29 examined various salivary cytokines in type 2 diabetics with the objective of comparing their data to healthy controls (Table 1). Salivary TNF-α was 1.9-fold greater in type 2 diabetics versus nondiabetics (P<0.049).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
See 1 more Smart Citation